Self-Actualization Measurement on Non-English Coastal Students’ Achievement: Rasch Model Analysis - Satria Agust; Gatot Subroto; Abdul Malik (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2018)
The measurement of self-actualization can assist facilitators in knowing their students’ learning achievement in English. The dynamism of high and low self-actualization through their origins will impact learning processes. Their abilities to seize the best achievement in learning correspond to their multiple talents. The objectives of this study are: (1) describing those whose self-actualization is high and who will have satisfactory achievement in learning English, and (2) deducing those whose self-actualization is low who will have poor achievement in English learning. The researcher used descriptive qualitative research which was conducted in Universitas Maritim Raja Ali Haji (UMRAH), located in Riau Archipelago in December 2017. The subject was the first-year intake of non-English students. The data were in the form of qualitative and quantitative taken from documents and questionnaires to learn the students’ self-actualization levels. The researchers analysed the data by using the Rasch model measurement approach. The results are: (1) Those whose self-actualization is high (60.71%) come from rural areas (36.90%), from urban areas (23.81%), female participants (47.62%), and male (13.10%). They can maximize their potential and ability to reach satisfactory achievement in learning English; and (2) Those whose self-actualization is low (38.10%), come from rural areas (17.86%), from urban areas (20.24%) female participants (33.33%), and male (4.76%). They cannot develop their potential and ability, resulting in poor achievement in learning English. As a result, the facilitators will find it easy to reflect on what should be done in their classes in the future.